DESAIN MEJA BELAJAR ANAK BERGAYA TETRIS - Andi Farid Hidayanto; Dyah Juliani Saputri Nur; Yohanes Firananta Setyo Atmono (Indonesian Society of Applied Science, 2023)
Early childhood age is in a stage of growth and development both physically and mentally. In their activities at school, children who study at the kindergarten level need learning facilities, one of which is study tables and chairs. Sometimes these facilities do not meet the condition of the student's body, dealing with its terms of size, shape and parts. The impact of the mismatch between the school fascilities such asa tables and chairs with the body size of school children is one of the obstacles in the efforts of improving learning outcomes. Tetris is one of the most favorite games that prioritizes competition among players, but still the players have to follows the rules of the game. This toy is quite interesting and popular among young children. Based on this background, efforts are made to solve the problem, one of which is by making tables and chairs for kindergarten children with the concept of the Tetris game. In designing products so that are well directed, the Vinod Goel method is used with the stages of Preliminary Design, Design Development, and Final Design and Prototype. The results of this design are intended for children aged 5 - 6 years, with components of chairs, tables, Tetris cubes and Tetris puzzles, with configurations according to ergonomics and anthropometry. The connection system uses a butt joint with nail reinforcement and glue adhesive. The material used is multiplex, with a shape of a tetris concept, a retro fifties and colorful design style with rainbow colors